A Study of Train to Pakistan Through a Different Perspective of Love and Sacrifice: Exploring Love and Sacrifice in the Midst of Religious Clashes (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Train to Pakistan also titled “Mano-Majra”. Khushwant Singh gives a detailed structure of love and affection of Sikhs and Muslims who lived together in peace for hundred years. The partition of India and Pakistan was one of the unfortunate and bloody religious clashes event in India. The people who love one another starts hating each other. Train is the most important symbol in the novel. With the changing description of train the tone of the novel also changed. After the news of the partition of India and Pakistan the killings started in Mano Majra the question arises who is responsible for this killings Hindus said that the Muslims had planned and started the killings followed by rape. But Muslims said that hindus were to blame. The fact was that both sid4es killed, both shot and stabbed, speared , chubbed , Tortured and raped. But in all this hatred some characters were there who live for humanity and who sacrifice their life only because to save life of others and the name of the character who live for humanity and died for others was Jaggu. (Jaggut Singh)Unlike other partition Novels, the major focus of the novel is not the killings. It is the feelings of love and compassion that we see and read on the pages of train to Pakistan.